Impact of environmental degradation on the development of moniliosis: A case study of apple orchards in the Almaty region, Kazakhstan - Zh.M. Isina; A.K. Koigeldina; A.K. Tursunova,; B. Kopzhassarov; A. Sardar; L.A. Boltaeva (Caspian Journal of Environmental Sciences)
Monilinia fructigena Pers is a specialized fungus known for its impact on pome crops, particularly during the fruiting phase. This pathogen is responsible for causing significant damage through fruit rot, affecting fruit quality and economic outcomes for growers. The primary objective of this research was to comprehensively investigate M. fructigena Pers, its distribution, and its effects on various fruit crops. Additionally, the study aimed to identify other fungal species associated with fruit rot and assess varietal resistance among different fruit tree varieties. Between 2021 and 2023, isolates of fungi belonging to the Monilinia genus were collected from fruits, inflorescences, shoots, and fruit formations of apple trees affected by moniliosis. Identification was conducted using polymerase chain reaction with species-specific primers and sequencing of the ITS 1-5.8S rRNA-ITS 2 locus of ribosomal DNA. The prevalence and impact of M. fructigena Pers and other identified fungi were analyzed. M. fructigena Pers was found to be the dominant fungus, with a frequency of occurrence ranging from 91.6 to 100%. This fungus was responsible for damage to inflorescences, shoots (monilial burn), and fruits (fruit rot). Other fungi, such as Fusarium proliferatum and Alternaria alternata, were also identified. Quarantine species M. fructicola was not found in the research orchards. In addition, varietal resistance experiments revealed differing susceptibility levels among apple tree varieties, with the Maksat variety being more susceptible than Voskhod. In conclusion, M. fructigena posed a significant threat to fruit crops, particularly pome varieties, in the studied regions. The research shed light on its prevalence, distribution, and impact. In addition, the identification of other fungal species associated with fruit rot provided valuable insights into disease management. The variable varietal resistance underscores the challenges of breeding for fruit rot resistance and highlights the importance of continued research in this area for more effective disease control strategies.